Rowan Williams’ Ecumenical Theology: a Response to Dame Mary Tanner - Rafferty SJ, Oliver P. (Ecclesiology, 2012)
Rowan Williams is among the best and most perceptive contemporary theologians in the English speaking world. Given his position as Archbishop of Canterbury, he is of necessity caught-up in the quest for Christian unity. His ecumenical theology can be discerned, however, not only in his directly ecumenical writings and speeches as Archbishop but also in his general theological approach. He emphasises Eucharist and baptism and whilst these may seem commonplace in ecumenical dialogue, nevertheless his analysis of the implications of baptism for believers offers something genuinely new in ecumenical thinking about the status of the baptised. Despite the difficulties in the present state of relations between the Anglican Communion and the Roman Catholic Church, Dr Williams’ theology does offer a hermeneutical tool that, if followed consistently by both churches, might enable the question of reunion to be placed in a different context, although of itself it cannot resolve the new problems that have been placed as obstacles on the road to corporate reunion.